The Application of Memorization and Play Methods to Increase Children's Interest in Learning at TPQ Bahrul Ulum - Ardiyansyah, Alizhar Tri; Murtiani, Rifqi; Rohmana, Wahyu Indah Mala (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research aims to examine the interest of children at the Bahrul Ulum Quran Education Park (TPQ) in learning using the memorization and play method. With the title